The use of polychaetes (Annelida) as indicator species of marine pollution: a review - Dean, Harlan K. (Revista de Biología Tropical, 2008)
Polychaetes are usually the most abundant taxon in benthic communities and have been most often utilized as indicator species of environmental conditions. This review finds that, while the use of indicator species for a particular pollutant is not simple, polychaetes can provide a useful means of assessing the effects of poor environmental conditions. Polychaetes may be used as sensitive monitors of water quality especially in terms of the effects of pollutants on life history characteristics. They may also be utilized as general indicators of community diversity but those species indicative of lower diversity may differ geographically and temporally. While sewage is often a mixture of high organic material and other pollutants such as heavy metals and pesticides, high organic situations associated with aquaculture facilities indicates that members of the Capitella capitata species complex and the dorvilleid genus Ophryotrocha are often dominant. Some species of polychaetes are able to live in sediments very high in trace metal content and body burden of these metals often does not reflect sediment concentrations due to regulation by these species. Many species seem relatively resistant to organic contaminants and pesticides and the effects of these pollutants on life history characteristics of these species may provide a more sensitive assay method. Recent studies using biomarkers in polychaetes to indicate general heavy metal or pesticide contamination has shown some success. Polychaete species known to occur in appreciable densities in the Gulf of Nicoya, Costa Rica, and which have been most often used as indicator species of pollution, are listed as potential taxa for environmental monitoring in this tropical estuary. Rev. Biol. Trop. 56 (Suppl. 4): 11-38. Epub 2009 June 30.